1999
DOI: 10.1183/09031936.99.13354199
|View full text |Cite
|
Sign up to set email alerts
|

Social factors associated with increases in tuberculosis notifications

Abstract: This study assessed the contribution of immigration and deprivation to the changes in tuberculosis notifications in Liverpool over the last 20 yrs. Ethnic origin was retrospectively assigned to all named cases from 1974 to 1995. Average tuberculosis rates were calculated for the 33 council wards in Liverpool for 1981-1985 and 1991-1995. Multiple regression was used to determine the independent effects of socioeconomic and population measures from the 1981 and 1991 censuses in explaining these ward-based rates.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 15 publications
0
5
0
4
Order By: Relevance
“…Prior studies have shown that the distribution of TB is heterogeneous in developed and developing countries and that this distribution is usually influenced by demographic, socio-cultural and geographic characteristics. 4,16 Tuberculosis constitutes a major health problem among indigenous populations in Brazil. The incidence of disease in these populations is high, and the rates of infection are up to ten times greater than those found in the general Brazilian population.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have shown that the distribution of TB is heterogeneous in developed and developing countries and that this distribution is usually influenced by demographic, socio-cultural and geographic characteristics. 4,16 Tuberculosis constitutes a major health problem among indigenous populations in Brazil. The incidence of disease in these populations is high, and the rates of infection are up to ten times greater than those found in the general Brazilian population.…”
Section: Discussionmentioning
confidence: 99%
“…La relación entre la TB y la privación social, la pobreza extrema, el hacinamiento y la indigencia ha sido descrita en otros estudios. En el Reino Unido se ha enfatizado la importancia de tener en cuenta tanto la privación como la inmigración de países en que la TB es una enfermedad común; aunque la privación y la inmigración están relacionadas, ambos tienen efectos sobre la distribución geográfica de la TB, sobre todo en los años más recientes 14,16,35,36 . En Estados Unidos el resurgimiento de la TB se ha relacionado con la infección por VIH, las toxicomanías, el hacinamiento, la inmigración y la indigencia 2 .…”
Section: Discussionunclassified
“…This is the reason BCG vaccinations were instituted at birth in many countries including Malaysia. However, statistics show that the majority of TB infections do not occur in children less than 16 years of age as the median age of infection in TB patients in the 1990s were at 49 -60 years in Caucasian patients and 31 -43 years in non-Caucasian patients [42]. Women, on the other hand, suffer severely with TB as TB is the third most common cause for mortality and morbidity in women aged 15 -44 from developing countries (higher than Malaria and AIDS) despite tuberculosis occurring less frequently amongst females [7] [43].…”
Section: Demographic Factors 221 Age Gender and Ethnicitymentioning
confidence: 99%